IMPLEMENTASI KEBIJAKAN PENATAAN PEGAWAI NON-ASN PADA RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU TAHUN 2024 - Putra, MHD. Aldi; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The policy on the arrangement of Non-Civil Servant Employees (Non-ASN) is part of the national bureaucratic reform agenda aimed at creating a professional, transparent, and accountable staffing system. This policy is regulated under Law Number 20 of 2023 on State Civil Apparatus and strengthened by Government Regulation Number 49 of 2018 on the Management of Government Employees with Work Agreements, which emphasize that all government institutions are required to complete the arrangement of Non-ASN employees no later than December 2024. The research method used in this study is a qualitative approach with a descriptive research type. Data collection techniques were conducted through interviews and documentation involving parties related to the policy implementation. Data analysis was carried out using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the Non-ASN employee arrangement policy at Rumah Sakit Jiwa Tampan Provinsi Riau has been carried out, but has not yet been fully optimal. This can be seen from several sub-indicators in the theory that have been implemented properly. However, obstacles were still found in the sub-indicator of the desired degree of change. In this aspect, the policy on the arrangement of Non-ASN employees should have been completed no later than December 2024. Nevertheless, in 2025 there were still 14 Non-ASN employees at RSJT Riau Province whose employment arrangements had not yet been completed. Therefore, it can be concluded that the desired degree of change has not been achieved optimally because there are still Non-ASN employees whose employment status has not yet been fully resolved. Keywords: Policy implementation, Non-ASN employee, structuring.